2023
DOI: 10.3389/fmicb.2023.1077561
|View full text |Cite
|
Sign up to set email alerts
|

Coping with salt stress-interaction of halotolerant bacteria in crop plants: A mini review

Abstract: Salinity is one of the major environmental abiotic stress factors that limit the growth and yield of crop plants worldwide. It is crucial to understand the importance of several adaptive mechanisms in plants toward salt stress so as to increase agricultural productivity. Plant resilience toward salinity stress is improved by cohabiting with diverse microorganisms, especially bacteria. In the last few decades, increasing attention of researchers has focused on bacterial communities for promoting plant growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Moreover, JPT10 may support osmotic equilibrium in foxtail millet seedlings during salt stress. PGPBs protect plants from salt stress damage through osmotic adjustment (de Andrade et al, 2023 ; Giannelli et al, 2023 ; Kumar et al, 2021 ; Kumawat et al, 2022 ; Ramasamy & Mahawar, 2023 ). The bacterial regulation of the concentration of trehalose, proline, and other osmolytes in plants is one of the mechanisms behind induced plant tolerance to desiccation (Ali & Khan, 2021 ; Sandhya et al, 2010 ; Yang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, JPT10 may support osmotic equilibrium in foxtail millet seedlings during salt stress. PGPBs protect plants from salt stress damage through osmotic adjustment (de Andrade et al, 2023 ; Giannelli et al, 2023 ; Kumar et al, 2021 ; Kumawat et al, 2022 ; Ramasamy & Mahawar, 2023 ). The bacterial regulation of the concentration of trehalose, proline, and other osmolytes in plants is one of the mechanisms behind induced plant tolerance to desiccation (Ali & Khan, 2021 ; Sandhya et al, 2010 ; Yang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hormone production is another important mechanism for PGPBs to protect plants against salt stress (de Andrade et al, 2023 ; Giannelli et al, 2023 ; Kumar et al, 2021 ; Kumawat et al, 2022 ; Ramasamy & Mahawar, 2023 ). Our findings support the notion that ABA influence the response to salt stress in foxtail millet since the elevated levels of them were caused by the combination of JPT10 and salt stress rather than salt stress alone (Figure 4b ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is crucial to accurately select suitable and efficient bioinoculants. 64 It should be noted that the efficiency of salt-tolerant plant growth-promoting rhizobacteria may vary depending on the climate in different ecological zones. 55 In field conditions, certain bacterial strains may exhibit an inability to successfully colonize the roots, resulting in a diminished capacity to promote plant growth compared to laboratory-controlled conditions.…”
Section: Saltwater In Inland Arid Landsmentioning
confidence: 99%
“…Regardless, there is increasing empirical evidence that, by implementing inoculations on a large scale, agricultural sustainability in the saline environment could be advanced. 64 It must be observed that, while promising, this practice is not without criticisms and is attracting growing attention as the market of soil microbial inoculants expands. Introducing microbial inoculants into new ecosystems raises concerns, as the release of alien species poses a potential risk of compromising ecological integrity and endangering indigenous communities vulnerable to introduced species.…”
Section: Saltwater In Inland Arid Landsmentioning
confidence: 99%
“…Endophytic bacteria that have the ability to colonize the inside the plants tissue is a subclass of plant growth promoting bacteria (PGPB). PGPB commonly known as plant growth-promoting rhizobacteria (PGPR) ( Palacios et al., 2014 ) are bacteria that boost plant development and promote soil bioremediation by secreting a variety of metabolites and hormones ( Peng et al., 2021 ), through nitrogen fixation ( Din et al., 2021 ), and by increasing other nutrients’ bioavailability through mineral solubilization ( Poria et al., 2022 ; Ramasamy and Mahawar, 2023 ). Diverse endophytic bacteria associated with sugarcane have been reported to affect their growth and development significantly ( Xing et al., 2016 ; Guo et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%